UJI AKTIVITAS ANTI JAMUR SEDIAAN SERUM EKSTRAK ETANOL DAUN PACAR (Impatiens balsamina L.) TERHADAP JAMUR Candida albicans SECARA IN VITRO - Indri Kusharyanti; Liza Pratiwi; Ayu Paramitha Anjani (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2026)
The normal flora on the scalp that can cause dandruff when excess oil is produced is Candida albicans. Chemical antifungal treatments for dandruff often cause side effects such as hair loss and headaches. Garden balsam leaves, which contain antifungal compounds like flavonoids, saponins, and alkaloids, can be extracted and formulated into hair serum as a natural alternative. This study aims to analyze the physical properties of the extract and serum from water henna leaves and evaluate their antifungal activity against Candida albicans. The evaluation involved physical property tests and in vitro disc diffusion using 2% ketoconazole shampoo as a positive control and serum without extract as a negative control. Tested concentrations were 1%, 3%, and 5%. Standardization of the extract showed a thick, dark brown liquid with a characteristic odor, a yield of 36.66%, water-soluble extract content of 78.66%, ethanol-soluble extract content of 70.09%, and moisture content of 2.51%. The serum showed increased color intensity, spreadability (4.63–5.3 cm), adhesiveness (3.49–41.91 seconds), pH (5.74–8.78), and viscosity (1016.6–1417.6 cPs). No inhibition zones were observed in the extract, serum, or negative control, while the positive control showed a strong inhibition zone of 46.03 mm.